A new approach for coupling external dynamics and internal mechanics in ship collisions. (January 2016) - Yu, Zhaolong; Amdahl, Jørgen; Storheim, Martin
Abstract: This paper proposes a new model, which efficiently couples the external dynamics and internal mechanics in ship collision accidents. This method is especially useful for design purposes since the detailed ship hull profile is not needed. Ship motions in the horizontal plane are considered. The collision forces are calculated using the explicit nonlinear finite element code LS-DYNA. The hydrodynamic forces in surge, sway and yaw are calculated using a traditional ship maneuvering model with a series of nondimensional coefficients determined from experiments. These forces are applied to the center of gravity (COG) of the ship with the user defined load subroutine in LS-DYNA and are solved together with structural response analysis during simulation. The proposed 3DOF coupled method was applied to calculations of an offshore supply vessel colliding with a rigid plate and a submersible platform. The results were compared with those predicted by a decoupled method. Ship motions with the proposed method compared reasonably with SIMO simulations. The advantages and limitations of the method were further discussed in the view of the equivalent added masses. Highlights: A simple procedure is proposed, which efficiently couples the external dynamics and internal mechanics in ship collisions. Ship motions in the horizontal plane compared reasonably with SIMO simulation results. Several ship collision cases are simulated with a rigid plate and a submersible platform. A comparative study is carried out with the decoupled method. The maneuvering model is discussed in the view of equivalent added masses.